Some strong limit theorems for arrays of rowwise negatively orthant-dependent random variables - Shen, Aiting (Journal of inequalities and applications, 2011)
In this article, the strong limit theorems for arrays of rowwise negatively orthant-dependent random variables are studied. Some sufficient conditions for strong law of large numbers for an array of rowwise negatively orthant-dependent random variables without assumptions of identical distribution and stochastic domination are presented. As an application, the Chung-type strong law of large numbers for arrays of rowwise negatively orthant-dependent random variables is obtained. MR(2000) Subject Classification: 60F15